EFFECT OF FARMING UNCERTAINTIES ON FOOD PRODUCTION: AN EMPIRICAL STUDY OF FARMER'S MOTIVATION IN THE ERA OF INSECURITY - Ibekwe, Franklin N. (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2022)
Farming uncertainties are critical features of the agricultural ecosystem. Indeed, previous studies have underscored various sources of agricultural uncertainties. However, little is known about security-related uncertainty and farmers' motivation. The present study examined the effect of farming insecurity on farmers' motivation. Two hundred and twenty-five farmers recruited from farming communities of Enugu State, Nigeria, completed a self-report instrument intended to ascertain their motivations relative to continuing farming activities in the perceived insecurities. A cross-sectional design was employed in the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, Version 23). Simple regression was run to test the main hypothesis that farming insecurity would predict farmers' motivation. The analysis demonstrated a statistically significant effect of farming insecurity on the farmers' motivation F (1,223), 21.31 P< .05, with the R2 indicating the independent variable accounted for 11.3% of the variation in farmer's motivation. The present finding contributes to the agricultural literature by revealing farming insecurity as a potential determinant of farmers' low motivations and the increasing low food production.